Evaluation of the Joint Village-Owned Enterprise Development Program at the Lamongan Regency Community and Village Empowerment Agency - Imelda Windy Aurelia; Niken Diah Wulandari; Paramitha Dea Rahmawati (Universitas Negeri Gorontalo, 2026)
The main issue underlying this study is the high amount of managed funds, which reached Rp 79 billion; ironically, however, the majority of BUMDesma are still in the pilot phase and are burdened by significant non-performing loans from women’s groups formerly associated with the PNPM program. The objective of this study is to comprehensively evaluate the effectiveness of the capacity-building program using the six criteria of William N. Dunn’s Evaluation Theory: effectiveness, efficiency, adequacy, equity, responsiveness, and relevance. This study employs a descriptive qualitative method, where data collection was conducted through interviews, observations, and documentation involving informants from the DPMD as well as beneficiary communities from two villages serving as a reality check. The results of the study indicate that the DPMD’s capacity-building efforts are highly responsive and administratively efficient, as evidenced by the successful acceleration of institutional legalization and the implementation of specific digital financial reporting through the SI DBM application. Nevertheless, this capacity-building program has not yet met the substantive criteria for effectively addressing the root causes of non-performing loans that have been outstanding for 5 to 15 years. This is due to a shift in community culture toward greater individualism, which has eroded the system of mutual responsibility, as well as the still-low level of digital literacy among village administrators. Furthermore, the vast geographical area and the limited number of field officers have resulted in the capacity-building program not being equitably distributed across all villages. In conclusion, the BUMDesma capacity-building program by the DPMD has proven successful in the realm of administrative governance, but it urgently requires a strategic shift toward a socio-cultural approach and more intensive technical capacity-building to restore the institution’s economic resilience in a sustainable manner.